Interpreters with Lewis and Clark : the story of Sacagawea and Toussaint Charbonneau - Nelson, W. Dale (Book collections on Project MUSE., 2003)
A frank portrayal of Toussaint Charbonneau, a French-Canadian fur trader, who, with his Shoshone Indian wife Sacagawea, joined the Lewis and Clark expedition in 1803. While Sacagawea assumed legendary status as a "token of peace", Toussaint has been maligned in fiction and nonfiction alike